2013
DOI: 10.1002/clen.201200391
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Artificial Agro‐Ecosystems Enhance Soil Carbon Sequestration in Coastal Zones of Southeast China

Abstract: Tidal flats, which are important reserved land resources, have a vital role in climate change. To evaluate the contribution of coastal saline soils to carbon sequestration, field tests were performed over a 3 year period at the Dafeng Wanggang Experimental Station in Jiangsu Province, China. Six artificial agro-ecosystems, including wasteland (WL), freshwater fish culture (FC), Sesbania culture (SC), barley culture (BC), mixed culture of fish and Sesbania (MCFS) and mixed culture of fish and barley (MCFB), wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is the specific form in the chemical denitrification and it is also closely related with NH 3 oxidation . NO 2 – is the substrate in the denitrification process . Many studies confirmed that non‐competitive NH 2 OH oxidation is associated with N 2 O emission .…”
Section: Introductionmentioning
confidence: 99%
“…It is the specific form in the chemical denitrification and it is also closely related with NH 3 oxidation . NO 2 – is the substrate in the denitrification process . Many studies confirmed that non‐competitive NH 2 OH oxidation is associated with N 2 O emission .…”
Section: Introductionmentioning
confidence: 99%
“…Yu, Zhang, Lu, et al [43] presented that the mean vegetation carbon density of the reed community was 2.35 kg m −2 and that of the lotus community was 0.26 kg m −2 in Nansi Lake. The paddy fields accumulated carbon via agricultural activities such as organic manure [24,44]. As showed in Table 2, the paddy fields had the highest available phosphorous and HF-N content.…”
Section: Effects Of Contemporary Land-use Types On Soil Organic Carbonmentioning
confidence: 99%